Painting after right-hemisphere stroke - case studies of professional artists - Bäzner, Hansjörg; Hennerici, Michael G. (Neurological disorders in famous artists - Part 2, 2007)
Changes in the style of professional artists as an immediate consequence of cerebrovascular disease are an intriguing phenomenon for the neuroscientist. While left-hemisphere damage is commonly provoking alterations in verbal production and comprehension, right-hemisphere stroke often leads to left-sided visuospatial neglect. We present a case series of 13 professional artists with right-hemisphere stroke and compare examples of their poststroke artwork with their prestroke artwork.